Aplicación de una auditoría ambiental a la empresa rosely flowers ubicada en la parroquia Aláquez, cantón Latacunga al período 01 de enero al 31 de diciembre del 2013 - Calvopiña Monge, Lorena Patricia (2015)
The present research has as main objective to evaluate compliance the Environmental Regulations, given that many companies do not give great importance to these factors directly reoffend environmental pollution in the country. For real and equitable information research techniques were used as the survey, interviews, questionnaires and fact sheets with which ones sufficient information was obtained. These techniques facilitated get real and concrete information on the situation the enterprise for compliance with Environmental Regulations. This research was of great importance for management since it could point out the drawbacks encountered in meeting the Standards, this research argues that many companies are unknown and Environmental Standards do not apply in the activities according to the Law and Regulation….